The Role of City Park as Public Spaces for Social and Recreational Activities A Case Study of Cattleya Park in West Jakarta - Ghefira Unggar Suci Fauziah; Purnomo Adi Saputro (Universitas Lambung Mangkurat, 2026)
Ruang Terbuka Hijau (RTH) or Green Open Space has an important role in maintaining the balance of urban ecosystems, improving environmental quality, and providing social interaction spaces for the community. The limited availability of Green Open Space in Jakarta, which only reaches 5.2% of the total area, is far below the national target of 30%, indicating the importance of Green Open Space as a vital element in creating a healthy and sustainable city. This condition also occurs in West Jakarta, which only has 0.45% of its area as green open space. One example of a developing public green space is Cattleya Park. This study aims to analyze the quality and quantity of facilities in Cattleya Park in supporting social and recreational activities, as well as to identify the challenges of its development as a sustainable public space. This research adopts a mixed-method design by integrating qualitative evidence from field observations and interviews with quantitative evidence gathered through Likert-scale questionnaires and a quantitative SWOT procedure. The results show that Cattleya Park has strengths in social, aesthetic, and recreational aspects, with a higher strength (S) score than weakness (W) score, namely 2.08:0.57 from the management side and 1.99:0.33 from the visitor side. External factors show that opportunities (O) are greater than threats (T), placing the park in quadrant I (growth/aggressive strategy). The main challenges include limited facilities, suboptimal drainage, and low community participation. With improved facilities, maintenance systems, and community involvement, Cattleya Park has the potential to become a sustainable and inclusive public space in West Jakarta.